Reguladores vegetais e nutrição mineral na formação de mudas de maracujazeiro-doce - Maciel, Glauco Henrique Pinheiro (Universidade Federal de São Carlos, 2018)
Crop plants have been widely used to discuss several physiological interactions between plant growth regulators (PGRs) and mineral nutrition. However, these physiological effects and their potentiality in non-domesticated species (wild species) are far to be elucidated. In this way, we hypothesized that PGRs and mineral element availability interactions guaranteed improvements in plant development under low availability for the establishment of Passiflora alata Curtis (sweet passion fruit) seedlings. We investigated plant growth and ionic accumulation of macro and micronutrients in leaf and root plant tissues of P. alata. As expected, the ionic accumulation of some elements (N, P, S, B, and Cu) increased in response to a higher nutrient solution (ionic strength, IS) availability. The interactions IS x PGR were significant with respect to almost all the plant growth variables, besides the Zn in leaf and N, Zn, and B in roots. By means comparisons, we verified that the plant growth responses and Zn in leaf were more similar between ISs when PGRs had been applied. Moreover, the use of PGR probably favors an adequate nutritional and hormonal balance, since it has guaranteed improvements even under low availability. We can conclude that Passiflora alata Curtis that did not receive these phytoregulators are more variable in terms of nutrient content, and are therefore more susceptible to nutritional deficiencies
Phytoregulators and mineral nutrition interactions to the establishment of Passiflora alata seedlings
Keywords: Fitorreguladores; Nutrição mineral; Passiflora alata; Solução nutritiva; Nutritional balance; Plant growth regulators; Plant nutrition; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL